2009
DOI: 10.1016/s1658-3876(09)50041-6
|View full text |Cite
|
Sign up to set email alerts
|

The National Oncology Program

Abstract: Cancer in developing countries is growing and will soon be a major problem as life expectancy increases. This article outlines the experience and future objectives of a partnership between Yemeni and Canadian oncology professionals in their attempt to develop a National Oncology Program in Yemen. We review current knowledge of the epidemiology, social, educational and economic challenges as well as suggested initial steps in developing a relevant oncology program for this society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Breast cancer in Yemen: Breast cancer is the most common cancer and the foremost cause of cancer death among women in Yemen. Breast cancer is the most common cancer (16.6%) of all cancers and of all female cancers (30.3%) in Yemen 2,3 . Local studies from the Sana'a, Aden and Hadhramaut regions of Yemen reported that breast cancer was classified as the number one cancer among Yemeni women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer in Yemen: Breast cancer is the most common cancer and the foremost cause of cancer death among women in Yemen. Breast cancer is the most common cancer (16.6%) of all cancers and of all female cancers (30.3%) in Yemen 2,3 . Local studies from the Sana'a, Aden and Hadhramaut regions of Yemen reported that breast cancer was classified as the number one cancer among Yemeni women.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015 there were about 1.7 million confirmed cases of breast cancer, resulting in some 521,900 deaths, worldwide 1 . In Yemen, breast cancer is recorded as the commonest cancer among women (30.3%) and the most common of all cancers (16.6%) 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…We have the expertise. Members of the Union for national oncology program in Yemen, 37 cervical cancer programs in Kenya and Mongolia, 38 cancer planning for East Africa and a breast centre in rural Bangladesh. 39 The Canadian branch of the International Network for Cancer Treatment and Research is engaged in cancer control in Brazil and palliative care in India, Nepal, Brazil and Tanzania.…”
Section: Opportunities For Canadians In Global Cancer Controlmentioning
confidence: 99%
“…The total number of registered cancer cases by the Ministry of Health was approximately between 20 000 to 25,000 cases of different cancers until 2018. However, the true cancer incidence in Yemen is unknown due to limited resources for pathology, the scarcity of epidemiological studies and the scarcity, and quality of medical records, and limited epidemiology resources [15]. Moreover, there are no early screening programs for most cancers, except for breast cancer which was introduced in 2005 (The National Cancer Control Foundation (NCCF)).…”
Section: Introductionmentioning
confidence: 99%